Demonstrating sexual selection by cryptic female choice on male genitalia: What is enough?. (1st November 2019) - Eberhard, William G.; Lehmann, Gerlind U.C.
Abstract: Rapid divergence in external genital structures occurs in nearly all animal groups that practice internal insemination; explaining this pattern is a major challenge in evolutionary biology. The hypothesis that species‐specific differences in male genitalia evolved under sexual selection as courtship devices to influence cryptic female choice (CFC) has been slow to be accepted. Doubts may stem from its radical departure from previous ideas, observational difficulties because crucial events occur hidden within the female's body, and alternative hypotheses involving biologically important phenomena such as speciation, sperm competition, and male‐female conflicts of interest. We assess the current status of the CFC hypothesis by reviewing data from two groups in which crucial predictions have been especially well‐tested, Glossina tsetse flies and Roeseliana (formerly Metrioptera ) roeselii bushcrickets. Eighteen CFC predictions have been confirmed in Glossina and 19 in Roeseliana . We found data justifying rejection of alternative hypotheses, but none that contradicted CFC predictions. The number and extent of tests confirming predictions of the CFC hypothesis in these species is greater than that for other generally accepted hypotheses regarding the functions of nongenital structures. By this criterion, it is reasonable to conclude that some genital structures in both groups likely involved sexual selection by CFC.